A clinical case of adjustment of venous access to a child with Pentalogy of Cantrell (Perioperaciina Medicina, 2019)
In the presented article, there is a clinical case of difficulties in the production of a venous catheter in a child with congenital malformation of the cardiovascular system (with an abnormal arrangement of blood vessels) There was described the catheterization of the right femoral vein with ultrasound navigation. Possible alternative ways of solving this problem were considered.
Keywords: central venous access; children; Ultrasound; Pentalogy of Cantrell